(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
In the article, the author analyzes the understanding of the meaning of the concept of old age in modern socio-psychological research based on: 1) the definition of the concept of old age and psychophysiological changes occurring at this stage of human development; 2) the formation of personality at this stage of age development; 3) the attitude of the aging person herself to the changes that occur to her, and 4) the stereotypes and social attitudes of modern society regarding old age and aging. The study concludes that research of the concept of old age is at the present stage of development of society one of the important ways to optimize interaction and social relations between people of different generations, as well as an important factor in the constructive psychosocial development of a person in the late period of his life.